STAT3 and Endothelial Cell—Cardiomyocyte Dialog in Cardiac Remodeling - Zouein, Fouad A.; Booz, George W.; Altara, Raffaele (Frontiers in Cardiovascular Medicine, 2019)
This article presents an overview of the central role of STAT3 in the crosstalk between endothelial cells and cardiac myocytes in the heart. Endothelial cell STAT3 has a key role in inflammation that underlies cardiovascular disease and impacts on cardiac structure and function. STAT3 in endothelial cells contributes to adverse cardiomyocyte genetic reprograming, for instance, during peripartum cardiomyopathy. Conversely, cardiomyocyte STAT3 is important for maintaining endothelial cell function and capillary integrity with aging and hypertension. In addition, STAT3 serves as a sentinel for stress in the heart. Recent evidence has revealed that the redox nature of STAT3 is regulated, and STAT3 is responsive to oxidative stress (ischemia-reperfusion) so as to induce protective genes. At the level of the mitochondrion, STAT3 is important in regulating reactive oxygen species (ROS) formation, metabolism, and mitochondrial integrity. STAT3 may also control calcium release from the ER so as to limit its subsequent uptake by mitochondria and the induction of cell death. Under normal conditions, some STAT3 localizes to intercalated discs of cardiomyocytes and serves to transmit pro-fibrotic gene induction signals in the nucleus with increased blood pressure. Further research is needed to understand how the sentinel role of STAT3 in both endothelial cells and cardiomyocytes is integrated in order to coordinate the response of the heart to both physiological and pathological demands.